Staying Down with the Joneses: Differences in the Psychological Cost of Unemployment across Neighbourhoods. (December 2022) - Howley, Peter; Knight, Sarah
This article demonstrates how the unemployment of neighbours can ameliorate the psychological costs of unemployment. In support of this premise, we find that while unemployment is always harmful, the gap in psychological well-being between employed and unemployed individuals is much less in relatively high unemployment neighbourhoods (particularly so for males and relatively older cohorts). Our proposed explanation is that people employ close points of social comparison with the result that any feelings of shame or embarrassment associated with unemployment are mitigated when surrounded by unemployed neighbours. One potentially important labour market implication of these findings is that it may be more difficult than anticipated to transition some people out of unemployment in high unemployment neighbourhoods. Apart from highlighting the place-specific nature of the relationship between unemployment and psychological well-being, our findings also highlight the importance of non-pecuniary factors, such as the social norm to work, in explaining the substantive negative psychological impact of unemployment.